Dinamika politik, ekonomi, dan administrasi Dinasti Umayyah - Wati, Linda; M, Amril (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This literature-based study revisits the political consolidation, fiscal innovation, and administrative reforms achieved by the Umayyad Caliphate (661–750 CE). Using a qualitative historiographical approach, it synthesises primary chronicles and recent academic works to expose three key developments: (1) transformation from elective caliphate to hereditary monarchy; (2) economic unification through Arabisation of currency and bureaucracy; and (3) layered administrative offices that standardised taxation, justice, and communication across a trans-regional empire. These findings show how how early government system, monetary policy, and institutional design under Muawiyah, Abdul Malik, and Umar II propelled unprecedented expansion yet simultaneously seeded structural weaknesses that precipitated decline. The article clarifies the caliphate’s dual legacy: state-building prototypes for later Muslim polities and cautionary lessons on centralised power; and suggests comparative avenues for future Islamic governance research.